DESKRIPSI KEMAMPUAN LITERASI NUMERASI SISWA SMP DITINJAU DARI GAYA BELAJAR. STUDI KASUS DI KOTA PADANG - Yerizon Yerizon; Arnellis Arnellis; Anna Cesaria (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Numeracy literacy is a skill that students must have in the independent curriculum (kurikulum merdeka). But in reality, the numeracy literacy skills of Indonesian students are generally low at every level of education. Because in the independent curriculum (kurikulum merdeka) the learning applied is the Differentiated Learning, it needs to be adapted to the learning style of the learners. For this reason, teachers must obtain an overview of the numeracy literacy skills and learning styles of students. The purpose of this research is to describe the numeracy literacy skills of junior high school students in terms of their learning styles. This type of research is descriptive qualitative research. The subjects in this study were seventh grade students spread across six public junior high schools. The instruments used were questionnaires and numeracy literacy tests. The data obtained were processed using two-way analysis of variance. From the results of the study it was found that in general the numeracy literacy skills of junior high school students were still low. There is no difference in the numeracy literacy skills of students based on learning styles but there are differences between schools. Learners with auditory style have better ability than visual and kinesthetic.